The effect of vortex trap on helicopter blade lift - Yaakub, Mohd Fauzi (2011)
The 5-seater Aerospatiale AS350B helicopter has been chosen in this analysis in order to investigate the capabilities of the vortex trap in increasing the helicopter blade lift. Blade Element Theory (BET) was applied to scrutinize the lift force and angle of attack distribution along the helicopter blade. From BET, the retreating blade must operate at a higher coefficient of lift for the purpose to balance the lift force on both sides of the rotor. In the process of designing and analyzing the grooyer, , commercial CFD, Fluent 6.3 and pre-processor Gambit were utilised in order to investigate the effect of groove which was applied on the upper surface of the helicopter airfoil. The Shear-Stress Transport (SST) k - o turbulence model was utilized in this analysis because of its capability in producing the flow inside the groove and the ability on predicting the separation of the airfoil. The mesh sensitivity analysis had also been accounted in the numerical study. The optimization of the groove was done by analyzing the numbers and locations of the grooves, the design depth and length of the groove and modification of the groove shape to smoothen the velocities flow. Finally, the data from BET was used with data from numerical analysis to obtain the lift force achieved by the vortex trap method to increase the lift of helicopter blade. Thus, the small increment of lift was achieved when applying groove on the upper surface of the retreating blade due to the small area contribution at high angle of attack